Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Connect with a community of experts ready to provide precise solutions to your questions on our user-friendly Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Let's solve the quadratic equation [tex]\(4x^2 + 12x + 9 = 0\)[/tex] using the quadratic formula and determine the correct substitution of the coefficients [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex].
The quadratic formula is given by:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
First, identify the coefficients [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex] from the given equation:
[tex]\[ a = 4 \][/tex]
[tex]\[ b = 12 \][/tex]
[tex]\[ c = 9 \][/tex]
Let's apply these values to the quadratic formula step-by-step.
1. Substitute [tex]\(a = 4\)[/tex], [tex]\(b = 12\)[/tex], and [tex]\(c = 9\)[/tex] into the formula:
[tex]\[ x = \frac{-12 \pm \sqrt{12^2 - 4(4)(9)}}{2(4)} \][/tex]
2. Calculate the discriminant ([tex]\(b^2 - 4ac\)[/tex]):
[tex]\[ b^2 - 4ac = 12^2 - 4(4)(9) \][/tex]
[tex]\[ = 144 - 144 \][/tex]
[tex]\[ = 0 \][/tex]
3. Substitute the discriminant back into the formula:
[tex]\[ x = \frac{-12 \pm \sqrt{0}}{8} \][/tex]
4. Simplify the square root and the expression:
[tex]\[ x = \frac{-12 \pm 0}{8} \][/tex]
[tex]\[ x = \frac{-12}{8} \][/tex]
[tex]\[ x = -1.5 \][/tex]
Since the discriminant is zero, there is exactly one real solution:
[tex]\[ x = -1.5 \][/tex]
Now let's match the correct substitution from the given options:
1. [tex]\( x = \frac{12 \pm \sqrt{12^2 - 4(4)(9)}}{2(4)} \)[/tex]
2. [tex]\( x = \frac{-12 \pm \sqrt{12^2 + 4(4)(9)}}{2(4)} \)[/tex]
3. [tex]\( x = \frac{-12 \pm \sqrt{12^2 - 4(4)(9)}}{2(4)} \)[/tex]
Comparing these options to our step-by-step substitution, we find that the correct substitution is given by:
[tex]\[ x = \frac{-12 \pm \sqrt{12^2 - 4(4)(9)}}{2(4)} \][/tex]
Therefore, the correct answer is:
[tex]\[ x = \frac{-12 \pm \sqrt{12^2 - 4(4)(9)}}{2(4)} \][/tex]
Thus, the correct option is:
[tex]\[ (3) \][/tex]
So, the solution to the quadratic equation [tex]\(4x^2 + 12x + 9 = 0\)[/tex] is correctly substituted in:
[tex]\[ x = \frac{-12 \pm \sqrt{12^2 - 4(4)(9)}}{2(4)} \][/tex]
The correct option that shows the correct substitution is [tex]\(\boxed{3}\)[/tex].
The quadratic formula is given by:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
First, identify the coefficients [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex] from the given equation:
[tex]\[ a = 4 \][/tex]
[tex]\[ b = 12 \][/tex]
[tex]\[ c = 9 \][/tex]
Let's apply these values to the quadratic formula step-by-step.
1. Substitute [tex]\(a = 4\)[/tex], [tex]\(b = 12\)[/tex], and [tex]\(c = 9\)[/tex] into the formula:
[tex]\[ x = \frac{-12 \pm \sqrt{12^2 - 4(4)(9)}}{2(4)} \][/tex]
2. Calculate the discriminant ([tex]\(b^2 - 4ac\)[/tex]):
[tex]\[ b^2 - 4ac = 12^2 - 4(4)(9) \][/tex]
[tex]\[ = 144 - 144 \][/tex]
[tex]\[ = 0 \][/tex]
3. Substitute the discriminant back into the formula:
[tex]\[ x = \frac{-12 \pm \sqrt{0}}{8} \][/tex]
4. Simplify the square root and the expression:
[tex]\[ x = \frac{-12 \pm 0}{8} \][/tex]
[tex]\[ x = \frac{-12}{8} \][/tex]
[tex]\[ x = -1.5 \][/tex]
Since the discriminant is zero, there is exactly one real solution:
[tex]\[ x = -1.5 \][/tex]
Now let's match the correct substitution from the given options:
1. [tex]\( x = \frac{12 \pm \sqrt{12^2 - 4(4)(9)}}{2(4)} \)[/tex]
2. [tex]\( x = \frac{-12 \pm \sqrt{12^2 + 4(4)(9)}}{2(4)} \)[/tex]
3. [tex]\( x = \frac{-12 \pm \sqrt{12^2 - 4(4)(9)}}{2(4)} \)[/tex]
Comparing these options to our step-by-step substitution, we find that the correct substitution is given by:
[tex]\[ x = \frac{-12 \pm \sqrt{12^2 - 4(4)(9)}}{2(4)} \][/tex]
Therefore, the correct answer is:
[tex]\[ x = \frac{-12 \pm \sqrt{12^2 - 4(4)(9)}}{2(4)} \][/tex]
Thus, the correct option is:
[tex]\[ (3) \][/tex]
So, the solution to the quadratic equation [tex]\(4x^2 + 12x + 9 = 0\)[/tex] is correctly substituted in:
[tex]\[ x = \frac{-12 \pm \sqrt{12^2 - 4(4)(9)}}{2(4)} \][/tex]
The correct option that shows the correct substitution is [tex]\(\boxed{3}\)[/tex].
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.